Cultural distance, memory and the perception of otherness: Chinua Achebe’s narratives as intercultural mediation (2015)
Cultural distance and cultural memory are two phenomena that are critical in intercultural dialogue and relations. This is because both are connected with the perception and management of difference in cultural knowledge, identity relations and representations. Intercultural relations between Europe and Africa have continued to be bogged down by the crisis of difference, asymmetry and inequality that engage the interest of African postcolonial narratives, for instance those of Chinua Achebe. This paper argues that Achebe's writing back to the empire through his narratives, Things Fall Apart and Arrow of God, rather than being seen only as a one-sided attack on Euro-Western chauvinism, is an act of intercultural mediation by an 'involved mediator', who engages cultural memory texts to reduce cultural distance and to call for mutual understanding and accommodation between African and European cultures.